RNAi screening reveals a synthetic chemical–genetic interaction between ATP synthase and PFK1 in cancer cells. Issue 4 (24th January 2023) - Kobayashi, Hiroki; Takase, Shohei; Nishimura, Haruna; Matsumoto, Ken; Harada, Hironori; Yoshida, Minoru
Abstract: To meet cellular bioenergetic and biosynthetic demands, cancer cells remodel their metabolism to increase glycolytic flux, a phenomenon known as the Warburg effect and believed to contribute to cancer malignancy. Among glycolytic enzymes, phosphofructokinase‐1 (PFK1) has been shown to act as a rate‐limiting enzyme and to facilitate the Warburg effect in cancer cells. In this study, however, we found that decreased PFK1 activity did not affect cell survival or proliferation in cancer cells. This raised a question regarding the importance of PFK1 in malignancy. To gain insights into the role of PFK1 in cancer metabolism and the possibility of adopting it as a novel anticancer therapeutic target, we screened for genes that caused lethality when they were knocked down in the presence of tryptolinamide (TLAM), a PFK1 inhibitor. The screen revealed a synthetic chemical–genetic interaction between genes encoding subunits of ATP synthase (complex V) and TLAM. Indeed, after TLAM treatment, the sensitivity of HeLa cells to oligomycin A (OMA), an ATP synthase inhibitor, was 13, 000 times higher than that of untreated cells. Furthermore, this sensitivity potentiation by TLAM treatment was recapitulated by genetic mutations of PFK1. By contrast, TLAM did not potentiate the sensitivity of normal fibroblast cell lines to OMA, possibly due to their reduced energy demands compared to cancer cells. We also showed that the PFK1‐mediated glycolytic pathway can act as an energy reservoir. Selective potentiation of the efficacy of ATP synthase inhibitors by PFK1 inhibition may serve as a foundation for novel anticancer therapeutic strategies. Abstract : We performed large‐scale RNAi screening to clarify the roles of phosphofructokinase‐1 (PFK1) in cancer cell proliferation and survival, and identified a chemical‐genetic interaction between genes coding subunits of ATP synthase (complex V) and PFK1. This study advances our knowledge of how cancer cells cope with their higher energy demand and provides insights into anti‐cancer therapeutics targeting cancer‐specific metabolism.